Indications of Factors Determining Corn Farmers' Behavior in Miomaffo Barat District, North Central Timor Regency, Indonesia - Falo, Marsianus; Kobesi, Petrus; Arimbawa, Putu (Universitas Panji Sakti, 2025)
Corn farmers on the RI–RDTL border frequently face limited resources in developing their agricultural potential, despite continuous government efforts to provide support and facilitation. Addressing this issue requires an understanding of both internal and external factors related to farmers, innovative characteristics, the role of information media, and the involvement of extension workers. This study aims to examine the determinants influencing maize farmers’ practices in West Miomaffo District, North Central Timor Regency. Data were collected through a survey of 161 corn growers and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The analysis revealed that communication efficacy and farmer-related external factors significantly influence behavioral changes, with critical ratio values exceeding the threshold (CR > 1.96). Conversely, internal farmer factors, innovation characteristics, and the role of extension workers did not have a significant effect on practice changes. These findings highlight that strengthening external support systems and improving communication strategies are more decisive for behavioral transformation among maize farmers in the border area than internal or innovation-driven factors.